ETNOMATEMATIKA PADA KUE KHAS ACEH SEBAGAI BAHAN PEMBELAJARAN MATEMATIKA - Asmaul Husna; Samsul Bahri; Rahmat Rahmat (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Ethnomathematics is a study of mathematics that implements culture in the teaching and learning process, especially in mathematics learning, can be an alternative in teaching mathematics and also introduces cultural values to students, especially in Acehnese cake culture. Most students do not realize that in everyday life they have applied mathematical concepts. This is because students only consider that mathematical concepts are only learned during mathematics subjects at school. This study aims to describe the ethnomathematics found in typical Acehnese cakes. This type of research is qualitative research with an ethnographic approach. The data collection method is observation conducted by 5 observers, interviews with 5 typical Acehnese cake makers, and documentation. The results showed that there is ethnomathematics in typical Acehnese cakes, namely being a medium for learning mathematics about the concepts of integers, fractions, awakening and congruence, building flat, and building space